Effect of Resistant Starch on the Gut Microbiota and Its Metabolites in Patients with Coronary Artery Disease - Kondo, Akihiko; Hirata, Ken-ichi; Sasaki, Kengo; Sasaki, Daisuke; Yamashita, Tomoya; Tabata, Tokiko; Osawa, Ro; Yoshida, Naofumi; Hayashi, Tomohiro; Fukuda, Hajime (Journal of Atherosclerosis and Thrombosis, 2019)
Aim: Bacteroides vulgatus and B. dorei have a protective effect against atherosclerosis, suggesting that expansion of these species in the gut microbiota could help patients with coronary artery disease (CAD). This study aimed to investigate the effect of resistant starch (RS) on the gut microbiota and its metabolites in fecal sample cultures from patients with CAD and individuals without CAD, using a single-batch fermentation system.Methods: Fecal samples from 11 patients with CAD and 10 individuals without CAD were fermented for 30 h with or without RS in the Kobe University Human Intestinal Microbiota Model (KUHIMM). Gut microbiota and the abundance of B. vulgatus and B. dorei were analyzed using 16S ribosomal ribonucleic acid (rRNA) gene sequencing and the quantitative polymerase chain reaction. Short-chain fatty acids were analyzed using high-performance liquid chromatography.Results: Gut microbial analysis showed significantly lower levels of B. vulgatus and B. dorei in the original fecal samples from patients with CAD, which was simulated after 30 h of fermentation in the KUHIMM. Although RS significantly increased the absolute numbers of B. vulgatus and B. dorei, and butyrate levels in CAD fecal sample cultures, the numbers varied among each patient.Conclusions: The effect of RS on gut microbiota and its metabolites in the KUHIMM varied between CAD and non-CAD fecal sample cultures. The KUHIMM may be useful for preclinical evaluations of the effects of RS on the gut microbiota and its metabolites.